Postgraduate nursing internationality education: A study in establishing an English nursing course - Yong‐bing Liu; Wei‐juan Gong; Xin‐e Mao (Wiley, 2020)
Abstract Aim The study was to explore the significant influence of an English nursing course in nursing postgraduate internationalization education. Design A cross‐sectional study. Method The research object included three grades (a total of 18) of nursing postgraduate students in the Nursing School of Yangzhou University. A standardized four‐section questionnaire designed by the authors was applied to the survey. Results 88.89% were satisfied with the course design and application of the English nursing course, and the scores for all 6 items were above the average, but only 44.4% of the postgraduate students understood the course completely. In teaching design and content aspect, 88.9%-94.4% postgraduate nurses felt that the course learning requirements were clear and could improve their knowledge and capacity for scientific research. All of the postgraduate nurses were identified with the teacher's moral and academic characters. Conclusions To establish English nursing courses for nursing postgraduate students is beneficial for postgraduate internationalization education.